From medicine price control to deregulation: assessing policy effects on insulin access in Pakistan’s private pharmacies - Amna Saeed; Minghuan Jiang; Najwa Ali Yasin; Jinran Zhao; Caijun Yang; Yu Fang; Zaheer-Ud-Din Babar (PLoS ONE, 2026)
Background Pakistan faces the highest global prevalence of diabetes and has recently implemented a price deregulation policy for medicines not listed on the National Essential Medicines List (NEML). Pakistan’s NEML 2023 is a direct adoption of the 23 rd WHO Model EML rather than a country-specific prioritization; nonetheless, it has been used to identify medicines for exemption from price controls. Methods This study evaluated the effect of the price deregulation policy on insulin access in Pakistan. We surveyed 30 retail pharmacies across six regions using an adapted WHO/HAI approach. Post-deregulation data on consumer prices and availability were collected. Pre-deregulation prices were extracted from published sources. The insulin prices were standardized to 10 ml at 100 IU/ml. Difference-in-Differences (DiD) analysis was used to compare price changes between non-NEML insulins (treatment group) and NEML-listed insulins (control group), with each insulin product serving as the unit of analysis. The percentage of available insulin products and their affordability for the lowest-paid worker were calculated. Non-parametric tests were performed for categorical analyses. Results Overall, the median price of insulins increased by 31.87% ( p < 0.001) i.e., from PKR 2030 (7.3 USD) to PKR 2678 (9.6 USD), after deregulation, except for short-acting human biosimilar (BS) insulins that stayed stable. As per the DiD-interaction term, prices of non-NEML insulins increased by 4.1 USD ( p < 0.001) more than NEML insulins after deregulation. The median number of days’ wages for the lowest-paid worker increased from 1.90 days before deregulation to 2.51 days after, to obtain a month’s insulin supply. All surveyed outlets had at least one insulin product available. Originator brands (OB) had higher availability than BS, with 78.0% of human and 48.8% of analogue insulins available as OBs, compared to 51.1% and only 8.3% as BS insulins, respectively. Conclusion Insulin prices increased significantly following the deregulation policy, particularly for non-NEML OBs, leading to reduced affordability despite fair availability. A policy review and stronger financial protection measures are needed to ensure equitable access to insulin.